2019
DOI: 10.1111/ssqu.12607
|View full text |Cite
|
Sign up to set email alerts
|

Can Crime Foster Social Participation as Conflict Can?*

Abstract: Objective Recent literature indicates that exposure to conflict can foster participation. Scholars often point to the social dynamics related to conflict to explain this finding. This article examines individual coping as alternative explanation. It should influence victims of violence independently of the origin of victimization. Methods Using data from four survey waves in Colombia conducted between 2013 and 2015 (N = 5,536), victims of conflict actors are compared to victims of common delinquency with fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Experiences of victimization elicit a vast array of emotions that eventually lead to an increase in pro-social behaviors and other forms of individual and collective participation, such as those based on cultural and artistic activities (see e.g., Bateson, 2012 ; Dorff, 2017 ; Oosterhoff et al, 2018 ; Nussio, 2019 ). However, the potential influence of self-perceived victimization on cultural participation (see e.g., Reyes-Martínez et al, 2020 ) and the influence of some types of cultural participation on the effects of victimization have been scarcely supported (see e.g., Bustamante, 2017 ; Gaitán and Segura, 2017 ).…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
“…Experiences of victimization elicit a vast array of emotions that eventually lead to an increase in pro-social behaviors and other forms of individual and collective participation, such as those based on cultural and artistic activities (see e.g., Bateson, 2012 ; Dorff, 2017 ; Oosterhoff et al, 2018 ; Nussio, 2019 ). However, the potential influence of self-perceived victimization on cultural participation (see e.g., Reyes-Martínez et al, 2020 ) and the influence of some types of cultural participation on the effects of victimization have been scarcely supported (see e.g., Bustamante, 2017 ; Gaitán and Segura, 2017 ).…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
“…Thus, we recommend conducting a cross-cultural study in countries with similar sociocultural conditions but with and without long-term internal conflicts (e.g., Colombia and Costa Rica). Such studies would also allow analyzing the potential confounding role of other sources of violence in Latin America (e.g., urban violence) and the outcomes observed in people exposed to armed conflicts (Nussio, 2019). In a study of this nature, it would be relevant to evaluate differences between civilians with low exposure of both countries, and between these civilians and active actors of the Colombian conflict to understand how these subtypes of aggression influence civilians.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies suggest that collective violence does not necessarily disrupt communities and that collective coping with the adversity of war may be much more common than traditionally assumed. For example, a recent meta-analysis (Bauer et al 2016) of nearly 20 studies conducted in over 40 countries has found a strong, persistent pattern that exposure to war violence tends to increase social cooperation at the local level, including community participation and prosocial behaviour (for similar findings see also Arjona et al 2016;Bellows and Miguel 2009;Fritz 1961Fritz / 1996Gáfaro et al 2014;Gilligan et al 2014;Nussio 2019;Vélez et al 2016). Why this occurs, however, is still poorly understood.…”
Section: Sandra Penic ´ John Drury and Zacharia Badymentioning
confidence: 99%